'Rethinking the way we practice our professions': social-ecological resilience for built environment professionals. Issue 1 (2nd January 2023) - Hurlimann, Anna; Beilin, Ruth; March, Alan
ABSTRACT: Urbanisation and industrialisation have contributed to significant and detrimental changes in the earth's natural environments. The concept of social-ecological resilience can assist this problem, by integrating the consideration of human and ecological systems in decision-making. An implication is that built environment professionals must be competent in social-ecological resilience knowledge and skills to ensure cities are well adapted to current environmental challenges, and do not further contribute to them. Yet the capabilities of built environment professionals to incorporate resilience thinking (theory and knowledge) into their work (skills and practice), is not well understood and is not well addressed in education theory. This paper contributes to this gap by: exploring the social-ecological resilience knowledge, skills, and practical experience of Australian built environment professionals, thereby identifying gaps to address in further and higher education. Results indicate that built environment professionals' know about social-ecological resilience, but they identify their practical experience is low. Additionally, respondents are more confident with their abilities, compared to colleagues, and their profession at large. The results indicate that further and higher education offerings (e.g. university education, continuing professional education, and practice) must assist built environment professionals to further develop social-ecological skills. As one respondent stated – it will require 'rethinking the way we practice our professions'.